Differences in patient-physician communication between the emergency department and other departments in a hospital setting in Taiwan - Yi-Fen Wang; Ya-Hui Lee; Chen-Wei Lee; Yu-Ze Shih; Yi-Kung Lee (BMC Health Services Research, 2023)
Abstract Background Communication fosters trust and understanding between patients and physicians, and specific communication steps help to build relationships. Communication in the emergency department may be different from that in other departments due to differences in medical purposes and treatments. However, the characteristics of communication in the clinical settings of various departments have not been explored nor compared. Objectives This study aimed to construct the steps in patient-physician communication based on the Roter Communication Model and compare communication performance between the emergency department and three other clinical settings—internal medicine, surgery, and family medicine departments. Methods Both qualitative and quantitative approaches were adopted. First, in-depth interviews were used to analyze clinical communication steps and meanings. Then, a quantitative questionnaire was designed based on the interview results to investigate differences in communication between the emergency department and the other three departments. Qualitative and quantitative data were analyzed from 20 interviews and 98 valid questionnaires. Results Patient-physician communication consists of four steps and ten factors. The four steps—greeting and data gathering, patient education and counseling, facilitation and patient activation, and building a relationship—had significant progressive effects. Patient education and counseling had an additional significant effect on building a relationship. The emergency department performed less well in the facilitation and patient activation, building a relationship step and the evaluation method, enhancement method, and attitude factors than the other departments. Conclusions To improve the quality of patient-physician communication in the emergency department, physicians should strengthen the steps of facilitation and patient activation to encourage patients’ active engagement in their health care.